Measurement of manufacturing agility: a case study. Issue 2 (18th May 2015) - Routroy, Srikanta; Potdar, Pavan Kumar; Shankar, Arjun
Abstract : Purpose: – The purpose of this paper is to determine the agility level of a manufacturing system along different timelines. Design/methodology/approach: – The fuzzy synthetic extents of agile manufacturing enablers (AMEs), on the basis of their importance, are determined. Then they are integrated with their performance ratings along different timeline for calculating the Fuzzy Agile Manufacturing Index (FAMI). Euclidean distances of FAMI from predetermined agility levels are mapped to determine the agility level of the manufacturing system along different timeline. Findings: – The proposed methodology was implemented in an Indian manufacturing organization to determine its agility level. It was concluded from the obtained results that there was significant improvement in the agility level along the timeline. Research limitations/implications: – The weights of the AMEs are assumed to be constant along the timeline. Practical implications: – The supply chain mangers can easily apply this methodology in their respective manufacturing organizations to assess and determine the agility level. This proposed approach will show the direction to check the performance of agility and evaluate the evolution of agility in their respective manufacturing organizations. Originality/value: – The combination of fuzzy synthetic extent of weights and average fuzzy performance ratings of AMEs to calculate the FAMI along the timeline considering judgments of multiple experts is a unique contribution.